Case Report: Neuronal Intranuclear Inclusion Disease With Oromandibular Dystonia Onset - Deng, Wei-Ping; Yang, Zhao; Huang, Xiao-Jun; Jiang, Jing-Wen; Luan, Xing-Hua; Cao, Li (Frontiers in Neurology, 2021)
Background: Neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative disease. Because of variable clinical manifestations, NIID was often misdiagnosed. According to published case reports, the common clinical manifestations of NIID include dementia, muscle weakness, autonomic impairment, sensory disturbance, rigidity, ataxia convulsions, etc. However, no cases of oromandibular dystonia were mentioned. Case Presentation: We describe a case of a 58-year-old woman presenting with mouth involuntary chewing initially. She started to show hand tremors, ataxia, and walking instability until 2 years later. Diffusion-weighted imaging showed high intensity signal along the corticomedullary junction. Fluid-attenuated inversion recovery imaging showed white matter hyperintensity. Electromyography (EMG) indicated peripheral nerve degeneration. Neuropsychological testing showed memory loss. Finally, skin biopsy and GGC repeat expansions in the NOTCH2NLC (Notch 2 N-terminal like C) gene confirmed the diagnosis of NIID. Conclusion: This case demonstrated that oromandibular dystonia could be the first symptom of NIID. This case report provides new characteristics of NIID and broadens its clinical spectrum.